ECOLOGY OF RUSSIAN POLITICAL DISCOURSE: PROBLEM STATEMENT - A. Bozhenkova, Natalia; A. Katyshev, Pavel; V. Ionova, Svetlana; N. Saakyan, Levon; M. Afanaseva, Elmira (Gênero & Direito, 2020)
The article offers a comparative description of typological mechanisms for political communicative practice and methods of verbal explication of its axiological and symbolic constituents, determining mental universals of individual/collective consciousness. The research position is based on the system multilevel analysis of the component structure of discourse in order to identify and characterize the linguistic and sociocultural dominants of political interaction, organized by a certain language system, taking into account the semiotic and literary-genre specifics of legitimate and illegitimate communicative acts. The methodological concept aimed at modeling institutional interactions in the context of ecological compatibility/toxicity of the transmission of ethno-sociocultural components of the universe allowed the authors to characterize the ways and mechanisms of representation and transformation of the sign structures of political communication, which determine the algorithms of verbal and discursive behavior. The combination of methods of discourse analysis, linguistic and cognitive projection, linguistic and cultural interpretations and functional-pragmatic consideration of text units made it possible to identify and qualify the linguistic and semiotic elements of legitimate/illegitimate political practices and to carry out the ecolinguistic typology of the basic linguistic components of political communication. The results of the study indicate a special communicative register of Russian political discourse, the markers of which are the processes of diffusion/recontextualization of language and persuasive techniques, semiotic consolidation of institutional reversion, various verbal indicators of social asymmetry (from metaphorization, euphemization, nominalization to the tactics of disintegration and manipulation), which not only actualizes the linguistic and cultural resources of ideologically marked discursive practices, but also significantly expands the area of possible communication risks. The modern political logosphere, as a part of the ecosystem, synergetically included in all spheres of human communication, forms new contextual concepts, stereotypes of assessments, norms (often limiting) of verbal behavior of all subjects included in it and communicative traditions of the universum as a whole.